Escala de Avaliação da Transferência do Cuidado Intra-Hospitalar (EATC): estudo metodológico - Machado, Andressa Teixeira (2024)
Introduction: The transfer of intra-hospital care is a complex and frequent practice that occurs daily in the daily routine of the nursing team. It is a complex process, which occurs through a set of actions that ensure coordination and continuity of assistance involving different actors. This involves possible risks to patient safety due to possible weaknesses in this process. Therefore, it is considered that assessments of care transfers are essential to maintain the quality of care provided. Objective: Develop and validate the content of a scale to assess the quality of intra-hospital care transfers carried out by nursing teams. Method: This is a methodological study in which five of the eight steps proposed by DeVellis were developed. The first step is determining what you want to measure. The second involves generating the group of items that will make up the study tool. These steps were based on a scoping review that brought support to enable theoretical deepening on the subject of patient transfer and the factors that are related to its quality. The third stage involves determining what you want to measure; The fourth stage is the evaluation of the instrument by expert judges, which had as participants 10 nurses, doctors from different regions of Brazil and 38 nursing professionals from a large hospital in southern Brazil to compose the pre-test. These data were analyzed using the Content Validity Index (CVI). The fifth stage involves reviewing the instrument based on the judges’ assessment. Results: The scoping review revealed that communication, patient transport, teamwork, patient participation, and the work process are factors related to the transfer of care. Based on this review, the first version of the Intra-hospital Care Transfer Assessment (EATC) scale was developed, containing 19 items that address practices that qualify care transfers. The evaluation of the scale by expert judges generated a CVI OF 0.9; 12 items had changes in wording, three were excluded and two were included. Version II of the instrument consisted of 18 items. This version, when applied to 38 nursing professionals, obtained a CVI of 0.97. Crombach's alpha was 0.78. Conclusion: EATC is considered valid by expert judges and the target audience. It consists of a tool capable of evaluating the quality of intra-hospital care transfers from the perspective of the nursing team.